Rethinking Race, Ethnicity, and the Assessment of Intercultural Competence in Higher Education - Gemma Punti; Molly Dingel (MDPI AG, 2021)
This qualitative study aims to explore the limitations of using a cultural assessment tool in higher education with the goal of preparing students to thrive in a highly demanding, diverse, and global community. Colleges and universities are potentially important sites of cross-cultural and cross-racial engagement and socialization, and cultural competence is arguably one of the critical skills that many higher education institutions are embracing to prepare students for our diverse, but increasingly polarized, global society. In particular, this study discusses the use of the intercultural development inventory (IDI), a cultural assessment tool that has not been validated in the U.S. for racial, ethnic, or social class differences, and which leaves out the role of structural inequalities in intercultural relationships. Findings reveal that interview data from black, indigenous, and people of color (BIPOC) did not align with their IDI results and that the tool dismisses the complex experiences of BIPOC students. These findings jeopardize the tool's purpose and validity. Finally, this study reveals the importance of educating students about structural competence to improve empathy and understanding of a diverse student body.